Opinion 2463: Ripiphorus Bosc, 1791 and Ripiphoridae Laporte, 1840 (Insecta, Coleoptera): generic and family-group names conserved by designation of a type species for the former - ICZN (Bulletin of Zoological Nomenclature, 2020)
The International Commission on Zoological Nomenclature has conserved the usage of the generic name Ripiphorus Bosc, 1791, type genus of Ripiphoridae Laporte, 1840, by designating Ripiphorus subdipterus Fabricius, 1792 as its type species.
Keywords: Nomenclature; taxonomy; RIPIPHORIDAE; Ripiphorus; Ripiphorus subdipterus